Pemanfaatan Pusat Sumber Belajar Perpustakaan dalam Meningkatkan Keterampilan Membaca pada Mata Pelajaran Bahasa Indonesia Peserta Didik Kelas IV MI Darussalam Kolomayan Wonodadi Blitar Tahun Ajaran 2023/2024 - Choirul Anwar; Angga Nuraufa Zamzami Saputra; Rista Farida (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2024)
The objective of this research is to describe the utilization of the learning resource center in the library for the Indonesian language subject at MI Darussalam Kolomayan Wonodadi Blitar for the 2023/2024 academic year and to describe the improvement in reading skills in the Indonesian language subject through the utilization of the library's learning resource center for fourth-grade students at MI Darussalam Kolomayan Wonodadi Blitar for the 2023/2024 academic year.